Propagation of Phaseolus albicarminus Debouck & N. Chaves, by layering, cuttings, and grafting. - Sabogal Carvajal, R.; Escobar Guzman, H.; Gereda, J.M.; Santaella, M.; Debouck, Daniel G. (2023)
P. albicarminus, endemic to Costa Rica and a wild relative of cultivated beans, was collected in 2012 and described in 2020 by Debouck et al. The Future Seeds germplasm bank, located in Palmira, Colombia, safeguards one accession (G40901) of this little-known bean. The availability of original seeds of P. albicarminus is limited and production of new seeds has been scarce.